(3GdeSGdcs - (3GdYGedj GdLYHj, GdTgjO GdKGfj, Rjf GdOjf Hf Ydj Hf CMeO, (B966 (3g`s
(3ChdgG (B:s
... (3cJGH GdVeGf (B.. (3bhdg hGdJYgO HGdeGd bO jchf eef Ydjg GdeVehf Yfg eGdg hbO dG jchf agfG KdGKI CbSGe CMO GdCbSGe GdJYgO HGdfaS gh GdcaGdI hGdJYgO HGdeGd eef djS dg Ydjg eGd gh GdVeGf HGdeYfi GdCNU heef Ydjg eGd gh GdMhGdI hajg Cfg SjCJj (B...s
(3BNQgG (B:s
.. (3hjMJed YOe HQGAJg HPdc dCUGdI YOe (B.. (3h(B^(3EfeG bHd aj Mb Gdhcjd dGSJFeGfg hgPG GdeYfi eabhO aj GdeTJQj EP dG jbHd bhdg aj Pdc dh cGf GdfRGY eYg GHJOGkA hfai GdYdGeI Yf gPG GdGMJeGd GdHCS aj GdJPcQI (B. (3Je GdeLdO GdKGfjs
(3JHUQI GdYfhGf (B:s
(3aj TQM TQGFY GdESdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\ 64s
(3GdPQjYI (B20\3516s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis